Strategies to Optimise the Quality of Nursing Care for Patients in Public Hospitals in the Bono Region, Ghana - Atinga, Ba-Etilayoo; Radana, Nolundi; ten Ham-Baloyi, Wilma (Africa Journal of Nursing and Midwifery, 2025)
The quality of nursing care plays a critical role in determining patient satisfaction and clinical outcomes. However, public hospitals in Ghana’s Bono region often struggle to meet the expected standards of care. This study aimed to develop strategies to enhance the quality of nursing care within these hospitals. An exploratory, descriptive, and contextual qualitative design was employed. The study was conducted in the Sunyani municipality, Bono region, across three purposively selected public hospitals—one municipal and two regional. Using multiple methods, underpinned by the Donabedian model of care, the study collected data through semi-structured interviews from a purposive sample of 18 patients, 18 nurses, and three nurse managers at three selected public hospitals, in addition to an integrative literature review. The findings were synthesised into a conceptual framework using Dickoff, James, and Wiedenbach’s theory development model, culminating in the creation of the I-CARE strategies. I-CARE (implementing organisational strategies, commitment to attributes and practices, augmenting outcomes, rendering holistic and patient-centred care, and enhancing resources and support) was reviewed and validated by six experts in nursing strategy and quality care. These evidence-informed strategies offer practical guidance for policymakers, hospital managers, and frontline nurses. Their implementation promises to transform nursing care delivery and significantly improve patient experiences and health outcomes across public hospitals in the region, but it requires further adaptation and testing.